EXPRESSIVES ILLOCUTIONARY IN MEME OF COVID-19 - Juanda (TALENTA, 2022)
This study discusses illocutionary expressive in the comic of COVID-19. Expressive speech acts are actions that express what is felt by the speaker, for example, such as statements of likes, dislikes, pain, sorrow, upset, and so on. The method used is descriptive method. The data sources used include https://twitter.com/ warstek.com/status/1239762134579343360?s=20. The results obtained are a form of disappointment with regulations during COVID-19 such as the lockdown rules, the rules for returning to the village, disappointment in seeing the conditions of lectures on campus, fear when watching news on television, and disappointment because the lockdown was extended. The impact of this research as a form of expression of public aspirations through mass media is increasingly open.